The Life Cycle of a Butterfly - Trumbauer, Lisa (Mankato, Minn. : Pebble Books, 2002)
Simple text and photographs present the life cycle of a butterfly.
Includes index.
Includes glossary.
Includes bibliography.
K-3
Accelerated Reader AR
Keywords: Butterflies -- Life cycles; Caterpillars